Breast cancer nutritional chemistry cachexia oncology - A clinical trials perspective - Swaminathan, Savitha; Ramalingam, Yamuna; Ranganathan, Balu; Jolius, Gimbun; Muthumariappan, S.; Mani, U. (CSIR-NISCAIR, 2020)
Breast cancer is the second largest killer disease among women globally. Annually approximately 48,000 women die of breast cancer. Breast cancer patients are at high risk of developing malnutrition from the underlying disease as well as from various drug regimen, chemotherapy and or radiotherapy interventions. As we work for personalized medicine for breast cancer, a personalized nutrition for breast cancer patients is much needed for their wellbeing both physiologically and psychologically. Most rather than all, of the treatment regimens possesses a concourse of side effects. An effective personalized nutritional therapy during and after cancer treatment leads to better quality of life for the breast cancer patients. Clinical trials are pivotal for any recommendations to be used at the commercial level upon approval of Food & Drug Administration. Several clinical trials have been carried out and many are now undertaken to come up with a significant upshot conclusion based on primary and secondary outcomes to show the after effects of particular nutrient supplements by increasing the overall survival or any other physiological upregulated / downregulated manifestation leading for a disease free survival. Docosahexaenoic acid and glutamine nutritional supplement has been reported to have beneficial effect for breast cancer patients in different clinical trials.